Firm Size Distribution and Employment Fluctuations: Theory and Evidence - Holger Görg; Philipp Henze; Viroj Jienwatcharamongkhol; Daniel Kopasker; Hassan Molana; Catia Montagna; Fredrik Sjöholm (Lund University, School of Economics and Management, Department of Economics, 2016)
This paper studies the effect of the firm-size distribution on the relationship between employment and output. We construct a theoretical model, which predicts that changes in demand for industry output have larger effects on employment in industries characterised by a distribution that is more skewed towards smaller firms. Industry-specific shape parameters of the firm size distributions are estimated using firm-level data from Germany, Sweden and the UK, and used to augment a relationship between industry-level employment and output. Our empirical results align with the predictions of the theory and confirm that the size distribution of firms is an important determinant of the relationship between changes in output and employment.
Keywords: E20; E23; L20; 330; Firm distribution; Firm size; Employment; Fluctuations